2018
DOI: 10.1080/10810730.2018.1533052
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Conflicting Health Warning Information on Intentions to Use E-Cigarettes -An Application of the Heuristic-Systematic Model

Abstract: The purpose of this study is to determine how nonsmokers perceive conflicting information when a modified risk statement is included along with a warning label on e-cigarette packages. We propose an application of the heuristic-systematic model to test whether this conflicting information leads to more or less active processing. As part of a larger inquiry into e-cigarette labeling, we present an experiment (n=303) in which we test this model with nonsmokers, measuring ambiguity perceptions, counter-arguing, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Misinformation and misperceptions (the belief that the misinformation claim is true) exist on a range of health issues and can be detrimental to effective treatment options or preventative health behaviours [27]. Misinformation and the inconsistency of health education has been seen to be detrimental in relation to a variety of public health messages including the uptake of childhood vaccinations [28], knowledge around the safe alcohol drinking levels in pregnancy [29], and understanding the risks and safety related to e-cigarettes [30]. The current study has shown that education may be an important factor in why pregnant women are less successful in adhering to NRT, but also how it can be used to assist women to use NRT effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Misinformation and misperceptions (the belief that the misinformation claim is true) exist on a range of health issues and can be detrimental to effective treatment options or preventative health behaviours [27]. Misinformation and the inconsistency of health education has been seen to be detrimental in relation to a variety of public health messages including the uptake of childhood vaccinations [28], knowledge around the safe alcohol drinking levels in pregnancy [29], and understanding the risks and safety related to e-cigarettes [30]. The current study has shown that education may be an important factor in why pregnant women are less successful in adhering to NRT, but also how it can be used to assist women to use NRT effectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that smokers perceived MRMs with a warning differently than nonsmokers. Indeed, Katz and colleagues [ 18 ] found that perceptions of ambiguity differed based on smoking status. Nonsmokers perceived MRMs with a warning as ambiguous, while smokers did not.…”
Section: Discussionmentioning
confidence: 99%
“…However, a combination of an MRM with a nicotine warning could result in a conflicting message (i.e., a message that both supports and opposes the same subject) and could be perceived as ambiguous [ 14 ]. Both qualitative [ 15 , 16 , 17 ] and quantitative studies [ 18 ] have documented such a possibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work on conflicting information and functional food, Naylor, Droms, and Haws (2009) describe the external environment as becoming more and more conflicting–opposing messages are conveyed in various media channels to influence consumer behavior. Although this topic is highly relevant, research on the effect of conflicting information on consumption is limited (Katz, Erkkinen, Lindgren, & Hatsukami, 2018; Naylor et al, 2009; Rogers & Gould, 2015).…”
Section: Introductionmentioning
confidence: 99%